A comparative study of judicial control in Iran, U.S.A and Canada - Jalalian, Askar (2015)
Supervision and control need tools and techniques that would usually take two forms: the first form is that the same court that hears claims and complaints submitted by the departments and its agents, handles other claims and all the claims are processed by these courts of justice. Another form of judicial supervision is supervision in a dual judicial system and that is a judicial system wherein only specialized courts are competent enough to review administrative claims and to investigate the conducts of the department and its agents. In this paper, we deal with how these tools are used in advanced legal systems like the U.S., and Canada and the Iranian legal system. The result we discover in the end is that in all stages of supervision by the supervisor and the supervised, there must be a sense of accountability to people and officials and this will be achieved by transparency in performance. In the absence of transparency supervision will be disrupted and some economic and admin